Efficacy of olocizumab in treatment of COVID-19 patients - T. V. Goma; A. N. Kalyagin; O. V. Ryzhkova; N. S. Soloveva (Acta Biomedica Scientifica)
Background. Production of pro-inflammatory cytokines including interleukin 6 (IL-6) is activated in COVID-19. Using olokizumab which inhibits IL-6 production in treatment of COVID-19 is pathogenetically justified.The aim. To study in real clinical practice the efficacy and safety of using the IL-6inhibitor (olokizumab) in treatment of patients with confirmed COVID-19 pneumonia.Materials and methods. The first group included 41 hospitalized patients with confirmed COVID-19 pneumonia having complex therapy including olokizumab. The control group consisted of 66 patients with confirmed COVID-19 pneumonia who did not have therapy with IL-6 inhibitor. We analyzed clinical (volume of lung involvement, respiratory failure degree, body mass index) and laboratory data (levels of T-troponin, lactate, procalcitonin, natriuretic peptide, C-reactive protein, fibrinogen, D-dimer, ferritin, erythrocyte sedimentation rate, glomerular filtration rate).Results. The groups did not differ in gender, age, body mass index of patients, volume of lung tissue injury, and duration of hospitalization (p > 0.05). Respiratory failure of 2–3rd degree was more common in patients of the first group (χ2 = 6.3; p = 0.010). The initial levels of C-reactive protein (50.9 [34.2; 76.2] and 32.2 [9.9; 69.1] mg/L respectively; p = 0.009) and fibrinogen (6.0 [5.3; 6.7] and 5.2 [4.3; 6.2] g/l respectively; p = 0.005) in patients having therapy including olokizumab were significantly higher than in the control group. The levels of erythrocyte sedimentation rate, fibrinogen and ferritin, D-dimer, detected upon admission of patients to the hospital, didn’t have statistically significant differences. At discharge, the erythrocyte sedimentation rate in patients receiving olokizumab was statistically significantly lower (9.0 [5.5; 14.5] and 13.0 [7.0; 27.0] mm/h; p = 0.018).Conclusions. Using olokizumab in the treatment patient with COVID-19 pneumonia has demonstrated a positive effect on clinical and laboratory parameters (erythrocyte sedimentation rate, fibrinogen level) in patients with pronounced inflammatory changes and respiratory impairment.